2005
DOI: 10.1590/s0103-84782005000300034
|View full text |Cite
|
Sign up to set email alerts
|

Determinação do índice de rigor-mortis e sua relação com a degradação dos nucleotídeos em tambaqui (Colossoma macropomum), de piscicultura e conservados em gelo

Abstract: Determination of the rigor-mortis index and its relation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Pedrazzani et al (2009) also found similar results when comparing the effect of two desensibility methods for Nile tilapia, wherein the rigor mortis has been reached between 8 and 9 hours after slaughter. Moreover, Batista et al (2004) and Almeida et al (2005) mentioned that when slaughtering specimens of matrinxã (Brycon cephalus) and tambaqui (Colossoma macropomum) respectively, rigor mortis was established much earlier, between 30 and 75 minutes. This suggests that the species respond differently on this parameter, which may be related among other factors to the slaughter method and the muscle fiber profile of each species.…”
Section: Rigor Mortismentioning
confidence: 99%
“…Pedrazzani et al (2009) also found similar results when comparing the effect of two desensibility methods for Nile tilapia, wherein the rigor mortis has been reached between 8 and 9 hours after slaughter. Moreover, Batista et al (2004) and Almeida et al (2005) mentioned that when slaughtering specimens of matrinxã (Brycon cephalus) and tambaqui (Colossoma macropomum) respectively, rigor mortis was established much earlier, between 30 and 75 minutes. This suggests that the species respond differently on this parameter, which may be related among other factors to the slaughter method and the muscle fiber profile of each species.…”
Section: Rigor Mortismentioning
confidence: 99%
“…Evaluating tambaqui quality (Colossoma macropomum), sacrificed by asphyxiation and kept on ice, the stage of full rigor occurred 30 minutes after slaughter [14]. For matrinxãs (Brycon cephalus) slaughtered and kept on ice, the stage of full rigor occurred at 75 minutes after death [15].…”
Section: Resultsmentioning
confidence: 99%